Rambellisea gigliensis and Rambellisea halocynthiae, gen. et spp. nov. (Lulworthiaceae) from the Marine Tunicate Halocynthia papillosa - Martina Braconcini; Susanna Gorrasi; Massimiliano Fenice; Paolo Barghini; Marcella Pasqualetti (Journal of Fungi, 2024)
In this study, 15 Lulworthiales strains isolated from the marine tunicate Halocynthia papillosa collected in the central Tyrrhenian Sea were characterized using a polyphasic approach (morpho-physiological, molecular, and phylogenetic analyses). Based on multi-locus phylogenetic inference and morphological characters, a new genus, Rambellisea, and two new species, R. halocynthiae and R. gigliensis (Lulworthiales), were proposed. Multi-locus phylogenetic analyses using the nuclear ribosomal regions of DNA (nrITS1-nr5.8S-nrITS2, nrLSU, and nrSSU) sequence data strongly supported the new taxa. Phylogenetic inference, estimated using Maximum Likelihood and Bayesian Inference, clearly indicates that Rambellisea gen. nov. forms a distinct clade within the order Lulworthiales. Moreover, the two new species were separated into distinct subclades, solidly supported by the analyses. This is the first report of Lulworthiales species isolated from animals.